2017
DOI: 10.1080/14656566.2017.1349100
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylating agents (HMA) treatment for myelodysplastic syndromes: alternatives in the frontline and relapse settings

Abstract: Introduction Hypomethylating agents (HMA) have played a pivotal role for treating myelodysplastic syndromes (MDS) over the past decade, inducing sustained hematological responses and delaying progression to leukemia. However, a vast majority of patients will experience treatment failure within 2 years, with poor prognoses and limited options, and management of this growing patient population remains unclear. Areas Covered With the introduction of new agents in the MDS field, a better understanding of the bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 92 publications
0
15
0
1
Order By: Relevance
“…After cellular uptake, AZA and DEC are incorporated into the DNA leading to inhibition of DNA methylation and reactivation of silenced tumor suppressor genes that cause tumor cell apoptosis/senescence. 18 Comparing these two HMAs, randomized trial data are lacking in demonstrating the superiority of either AZA versus DEC. 19 There is some expert consensus that AZA may be preferable to DEC given the phase III AZA-001 study found AZA significantly improved OS compared to conventional care regimens (best supportive care, low-dose cytarabine, or intensive chemotherapy) of 24.5 months versus 15 months, respectively, 20 whereas, low-dose DEC compared with best supportive care had no significant difference in OS with 10 months versus 8 months, respectively. 21 However, it must be noted that the dose of DEC used in this study was 15 mg/m 2 IV three times a day for 3 days in 6-week cycles rather than the current FDA-approved dosing schedule of DEC 20 mg/m 2 /day IV for 5 days every 4 weeks.…”
Section: Clinical Outcomes Of Mds and Unmet Needsmentioning
confidence: 99%
“…After cellular uptake, AZA and DEC are incorporated into the DNA leading to inhibition of DNA methylation and reactivation of silenced tumor suppressor genes that cause tumor cell apoptosis/senescence. 18 Comparing these two HMAs, randomized trial data are lacking in demonstrating the superiority of either AZA versus DEC. 19 There is some expert consensus that AZA may be preferable to DEC given the phase III AZA-001 study found AZA significantly improved OS compared to conventional care regimens (best supportive care, low-dose cytarabine, or intensive chemotherapy) of 24.5 months versus 15 months, respectively, 20 whereas, low-dose DEC compared with best supportive care had no significant difference in OS with 10 months versus 8 months, respectively. 21 However, it must be noted that the dose of DEC used in this study was 15 mg/m 2 IV three times a day for 3 days in 6-week cycles rather than the current FDA-approved dosing schedule of DEC 20 mg/m 2 /day IV for 5 days every 4 weeks.…”
Section: Clinical Outcomes Of Mds and Unmet Needsmentioning
confidence: 99%
“…The HMAs AZA and DEC [as well as guadecitabine (SGI-110; a decitabine analogue that is not metabolized by cytidine deaminase and therefore has an extended half-life)] act as DNA methyltransferase inhibitors and lead to demethylation of DNA in a cell-cycle-dependent manner. 27 This has been shown to restore the transcription of previously silenced genes and leads to clinical benefit in patients with myeloid neoplasms. 11 , 15 , 28 , 29 Selected clinical trials of HMA monotherapy in MDS are summarized in Table 1 .…”
Section: Hypomethylating Agents In Mds Treatmentmentioning
confidence: 99%
“…Transfusion-dependent patients with low-risk MDS may receive lenalidomide, low-dose hypomethylating agents (HMAs), erythroid-stimulating agents, and/or iron-chelating therapy based on disease subtype and treatment history [ 1 ]. For patients with higher-risk MDS, hematopoietic stem cell transplant is currently the only potential curative option, whereas HMAs are standard of care for transplant-ineligible disease [ 3 , 4 ]. Quality-of-life is compromised as assessed by functional and disease-specific components, including significant fatigue levels [ 5 – 7 ].…”
Section: Introductionmentioning
confidence: 99%